Layered double hydroxides-indomethacin nanohybrids : intercalation, pH influence, stability and release properties - Mendieta, Silvia Nazareth (2016)
Fil: Mendieta, Silvia Nazareth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigación y Tecnología Química; Argentina.